Nutritional characterization of the extrusion-processed micronutrient-fortified corn snacks enriched with protein and dietary fiber - Shah, Faiz-ul-Hassan; Sharif, Mian Kamran; Ahmad, Zulfiqar; Amjad, Adnan; Javed, Muhammad Sameem; Suleman, Raheel; Sattar, Dur-e-Shahwar; Amir, Muhammad; Anwar, Muhammad Junaid (Frontiers in Nutrition, 2022)
The current study focused on developing protein- and dietary fiber-enriched, micronutrient-fortified corn snacks using extrusion technology. Corn, soybean, and chickpea flour were used to develop micronutrient-fortified (Fe, Zn, I, and vitamin A, and C) extruded snacks, followed by an exploration of their nutritional traits. Soybean and chickpea were supplemented discretely (20–40/100 g) or in a combination of both (10:10, 15:15, and 20:20/100 g). According to the results, the relative proportion of the raw material composition was reflected in corn snacks' proximate composition and mineral and vitamin levels. Corn snacks with 40/100 g soy flour showed the best nutrient profile, with a maximum percent increase in protein (171.9%) and fiber (106%), as compared to the snacks developed using chickpea and/or mixed supplementation with soy and chickpea. Total dietary fiber (18.44 ± 0.34%), soluble dietary fiber (10.65 ± 0.13%), and insoluble dietary fiber (7.76 ± 0.38%) were also found to be highest in the soy-supplemented snacks (40/100 g). It was discovered that 100 g of corn snacks could provide 115–127% of the RDA for iron, 77–82% of the RDA for zinc, 90–100% of the RDA for vitamin A, and 45–50% of the RDA for vitamin C. The results for the effect of extrusion processing on amino acids showed a 2.55–45.1% reduction in essential amino acids, with cysteine and valine showing the greatest decrease and leucine and tryptophan remaining relatively stable during extrusion.